Body structure profiles of R. of Serbia's senior handballers from different competitive levels as measured by the multichannel bioelectric impedance method - Dopsaj, M.; Valdevit, Z.; Ilic, D.; Pavlovic, L.; Petronijevic, M. (Facta Universitatis: Series Physical Education and Sport, 2017)
The goal of this study was to define body composition characteristics and differences between Serbian male handballers measured by the multiple bioimpedance method. The sample of subjects consisted of 94 male senior handballers from three different competition levels, distributed as follows: the Serbian male national team = 19; the Serbian Super National League = 43; and the Serbian First National League = 32. Twenty-two (22) variables were measured in this research, structured as follows: eight (8) basic and fourteen (14) derived or index variables, with six (6) of the latter being dependent on body voluminosity, seven (7) dependent on body longitudinality, and one (1) was an index variable. For all the results, descriptive statistical characteristics were calculated and multivariate and univariate analysis of variance (MANOVA and ANOVA) were used to establish both general and partial potential inter-group differences, by applying Wilks`s Lambda criterion. The results of the MANOVA showed, in general, statistically significant differences in the examined body composition variables between samples of handballers at Wilks's Lambda Value 0.370, F = 2.048, p = 0.001. Established differences explained 39.2% of the general variability (Partial Eta2 =0.392) with the observed statistical power of the data of 100% (Observed Power = 1.000). The statistically significant variables that predominantly defined body composition differences, were: BH, BM, Proteins, Skeletal Muscle Mass, Minerals, Total Body Water, Free Fat Mass and Muscle Mass Index (p = 0.000). The findings of this study show a statistically varied body composition of handballers of different competitive success; in other words, the most successful players, or players in the ranks of the Serbian national team, morphologically differ from players in lower competitive ranks. Also, the findings show that the multiple bioimpedance method is valid in defining the mentioned body composition differences for handball players of different competitive success, and therefore it can be used, both in general and in particular, in practice and in the science of handball. In respect to the partitioning of the initial variables, the findings have shown that this partitioning for defining the differences between the observed samples is somewhat more handball, body composition, males, bioimpedance. sensitive than the one in respect to the bodily height, i.e., longitudinality.